CARE FOR POTENTIAL BRAIN-DEAD ORGAN DONORS IN AN ADULT EMERGENCY ROOM: A CONVERGENT CARE PERSPECTIVE. - Lovato Flores, Cíntia Maria; da Silva, Rosângela Marion; Tamiozzo, Juliana; Flores Coelho Centenaro, Alexa Pupiara; Guerreiro Vieira da Silva, Denise Maria; Zamberlan, Cláudia; Camponogara, Silviamar (Texto & Contexto Enfermagem, 2023)
Objective: to investigate situations that interfere with health professionals' performance, in the identification and maintenance of potential brain-dead donors in an Adult Emergency Care Unit, and to indicate actions, from the health team's perception, that can promote care for these patients. Method: this is a qualitative, convergent care research, carried out with health professionals from an adult emergency unit, a large public teaching hospital located in southern Brazil. Data were collected between February 2020 and January 2021 through structured participant observation, semi-structured interview and convergence group. Data analysis was performed according to the stages of gathering, synthesis, theorization and transfer. Results: based on data analysis, the difficulties in caring for brain-dead persons, lack of information, inadequate structure and difficulties in the work process were identified as situations that interfere with health professionals' performance in relation to brain-dead potential donors. Actions were signaled to promote care for these people through continuing education activities on the subject, dissemination of information, construction of technologies/protocols, organization of infrastructure and the work process with support for professionals who assist these people. Conclusion: it was evidenced that professional education, the organization of the donation process and systematized actions to improve the work are fundamental factors for the effective care for brain-dead potential organ donors.